Role of Bioelectricity During Cell Proliferation in Different Cell Types - Bhavsar, Mit Balvantray; Leppik, Liudmila; Costa Oliveira, Karla Mychellyne; Barker, John H. (Frontiers in Bioengineering and Biotechnology, 2020)
Most living organisms possess varying degrees of regenerative capabilities but how these regenerative processes are controlled is still poorly understood. Naturally occurring bioelectric voltages (like Vmem) are thought to be playing instructive role in tissue regeneration, as well as embryonic development. The different distribution of ions on the either side of the cell membrane results in intra- and extra-cellular voltage differences, known as membrane potential or Vmem. The relationship between Vmem and cell physiology is conserved in a wide range of cell types and suggests that Vmem regulation is a fundamental control mechanism for regeneration related processes e.g. proliferation and differentiation. In the present study we measured Vmem in three different cell types (human osteogenic sarcoma cell line (OSC), rat bone marrow derived mesenchymal stem cells (BM-MSC), and rat dermal fibroblasts) and characterized the relationship between their Vmem and proliferation. In order to find out if Vmem controls proliferation, or visa-versa, we blocked and then unblocked Vmem (Na+/K+-exchanging ATPase) using ouabain and measured the proliferation. Our results demonstrate that Vmem can be pharmacologically manipulated to control proliferation in certain cell types like BM-MSC. Taken together, it is clear that control of bioelectrical properties in non-excitable cells could prove to be potentially a useful tool in regenerative medicine efforts.